Nivel de conocimiento sobre medidas preventivas en salud oral en estudiantes de estomatología de la Universidad Nacional de Trujillo, 2019 - Castillo Castillo, José Abelardo (2020)
This basic, descriptive and cross-sectional study was aimed to determine the level of knowledge about oral preventive oral health measures in stomatology students of the National University of Trujillo in 2019. The study population consisted of 71 students, of which 68 were respondents, 2 students dropped out of the career; 44 female (64.71%) and 24 male (35.29%); 21 students correspond to the third year (30.88%), 23 students to the fourth year (33.82%) and 24 students correspond to the fifth year (35.29%), to whom was applied a survey questionnaire validated by expert opinion. The results reveal that the level of knowledge about oral preventive oral health measures in students of stomatology was 77.9% whit “”Good” level and 22.1 whit “Regular” level. On the other hand, in each of years study and also in each gender predominates the “Good” level. It is concluded that the level of knowledge about oral preventive oral health measures in stomatology students of the National University of Trujillo in 2019 was “Good”. It was found that there is a significant statistical difference between the level of knowledge and years study, while that there is no difference between the level of knowledge and gender.